Intolerance: Religious Practices in Social Media Platform X - Erisa Nada Dewanti; Ita Rodiah (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2025)
Religious intolerance is a contemporary issue in Indonesia considering that Indonesia is a pluralistic country that has various religions and beliefs. Conflicts and issues of religious intolerance have existed for a long time. However, with the emergence of social media, people can easily spread content containing religious intolerance which causes conflict between religious communities. This article aims to examine in more depth the causes and consequences of the upload by X’s account. This research uses qualitative methods with data in the form of opinions, comments, criticism, and reasons from user X's uploads and comments. The results of this research show that the causes of intolerance in religion, and 3) attitudes of fanaticism and exclusivism. To avoid religious intolerance, we should be wiser in using social media and expressing opinions. Don't swallow the information you receive, look for facts first, and increase your knowledge and knowledge of religion so you don't become a disseminator of religious intolerant content.